(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The article deals with the description and analysis of what competences and personal features will be required in the future. The purpose of this article is to discuss an important issue regarding the competence that a specialist of the 21st century should have. In a world of rapid and unpredictable changes, it’s vital that young people are equipped with the right skills and competences to be prepared to respond to the challenges of the society. These are the competences that are necessary for a specialist of the future: understanding situations and circumstances (Sense making); social intelligence (Social intelligence); adaptive thinking (Adaptive thinking); intercultural competence (Cross cultural competence); algorithmic thinking (Computational thinking); interdisciplinary thinking (The ability to understand concepts across multiple disciplines); design thinking (Design mind-set) and virtual collaboration (Virtual collaboration). The individuals who develop these skills are qualified as knowledge workers. They will be able to operate in changing environments, to handle non-routine and abstract work processes, to make decisions or assume responsibilities, to work and interact as a team, and they will achieve a broad and systemic understanding. Key words: competence; sense making; social intelligence; intercultural; design thinking; virtual collaboration.